Nutrition : maintaining and improving health - Webb, Geoffrey P. (Boca Raton : CRC Press, 2020)
"This fifth edition offers comprehensive treatment to the role of diet in causing, preventing, and treating chronic disease and maintaining good health. Aimed at introductory undergraduates, the textbook includes key points throughout textboxes, introduction/aims of the chapter, and concluding remarks"--
Changing priorities in nutrition -- Food selection -- Methods of nutritional assessment and surveillance -- Investigating links between diet and health outcomes -- Investigating links between diet and health : amalgamation, synthesis and decision making -- Dietary guidelines and recommendations -- Introduction to energy aspects of nutrition -- Energy balance and its regulation -- Obesity -- Carbohydrates -- Protein and amino acids -- Fat -- Dietary supplements and food fortification -- Food as medicine -- The vitamins -- The minerals -- Nutrition and the human life-cycle -- Nutrition as treatment -- Some other groups and circumstances -- The safety and quality of food.
OCLC-licensed vendor bibliographic record.
Keywords: Nutrition; MEDICAL / Clinical Medicine; MEDICAL / Nutrition; TECHNOLOGY / Food Science